Ultrasound-Guided Analgesia in Cardiac and Breast Surgeries: A Cadaveric Comparison of SPIP Block with Single and Double Injections vs. DPIP Block - Carmelo Pirri; Debora Emanuela Torre; Astrid Ursula Behr; Veronica Macchi; Andrea Porzionato; Raffaele De Caro; Carla Stecco (Life)
The evolution of regional anesthesia techniques has markedly influenced the management of postoperative pain, particularly in thoracic surgery. As part of a multimodal analgesic approach, fascial plane blocks have gained prominence due to their efficacy in providing targeted analgesia with minimal systemic side effects. Among these, the superficial intercostal plane (SPIP) block and deep parasternal intercostal plane (DPIP) block are of notable interest. The aim of this study was to investigate the dye spread to the anterior chest wall space and its spread pathway through anatomical morphometric analyses on cadavers for single-injection and double-injection SPIP blocks versus DPIP blocks. In both qualitative and quantitative evaluations, the single-injection SPIP block with 10 mL of dye demonstrated a broader and more extensive spread compared to the double-injection SPIP block, which used 5 mL of dye per injection site (p < 0.05), and the DPIP block with 10 mL of dye (p < 0.05). All the blocks had a positive correlation between the distances from the sternum border and the area of dye spread, suggesting that the crucial role of volume in fascial blocks is that it significantly affects the opening of the fascial compartment, enabling optimal spread of the anesthetic. Adequate volume facilitates proper spread and diffusion across the fascial plane, ensuring more comprehensive fascia coverage and thus enhancing the block’s effectiveness. Finally, precise volume management is key to maximizing both efficacy and safety.